Nutrients, oxygen and biogeochemical processes in the Humboldt upwelling current system off Peru - Graco, Michelle I. (2007)
The upwelling system of the Humboldt Current, is considered among the most productive systems in the world, extending along the eastern South Pacific off Chile and Peru. In particular the coastal waters off Peru attracted considerable interest for being among the most fertile and productive the world, highlighting fisheries, such as anchovy, which represent one of the pillars of the economy of Peru.